(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the early outcomes of pancreaticojejunostomy using a modified Blumgart technique reinforced with the falciform ligament in patients undergoing pancreaticoduodenectomy. Methods: A retrospective descriptive study was conducted on 25 patients who underwent pancreaticoduodenectomy with reconstruction using a modified Blumgart pancreaticojejunostomy reinforced with the falciform ligament at the Department of Oncology and Radiotherapy, Viet Duc University Hospital, between May 2023 and December 2023. Results: The study included 25 patients (12 male, 13 female) with a mean age of 60.32 ± 13.17 years. Pancreatic head tumors were the most common indication (40%). A falciform ligament flap with a mean size of 71.04 × 24.96 mm was used in all patients. Soft pancreatic texture was observed in 68% of cases, and the mean pancreatic duct diameter was 3.12 ± 0.64 mm. Pancreaticojejunostomy was performed using three transpancreatic U-sutures in 92% of patients, with a mean anastomotic time of 24.08 ± 6.15 minutes. The mean operative time was 423.76 ± 116.78 minutes. Biochemical pancreatic fistula (grade A) occurred in 28% of patients, while one patient (4%) developed grade B postoperative pancreatic fistula associated with gastrointestinal bleeding. No cases of biliary leakage, delayed gastric emptying, intra-abdominal hemorrhage, pancreatic parenchymal tearing during anastomosis, intra-abdominal abscess, or postoperative mortality were recorded. The mean hospital stay was 14.72 ± 4.70 days, and favorable outcomes at discharge were achieved in 96% of patients. Univariate analysis identified BMI ≥ 23 kg/m², soft pancreatic texture, operative time > 8 hours, and pancreatic stump thickness > 12 mm as factors associated with postoperative pancreatic fistula. Conclusions: Pancreaticoduodenectomy with modified Blumgart pancreaticojejunostomy reinforced by the falciform ligament demonstrated favorable early outcomes, with a low rate of clinically relevant postoperative pancreatic fistula and no postoperative mortality.